PENGARUH PENGGUNAAN TEKNIK ASSERTIVE TRAINING UNTUK MEREDUKSI KONFORMITAS TEMAN SEBAYA DI SMP SWASTA PUTERI SION MEDAN - Renova Fransisca Adeline; Anita Yus (JURNAL TEMATIK, 2019)
This study aims to determine adolescent conformity behavior and attainment of adolescent self-identity through Assertive Training Techniques. This type of research is experimental research. The results showed that there was an influence on the use of assertive training techniques to reduce peers' conformity in class VII Puteri Sion Medan Medan. The average score of peer conformity scores at the pre-test = 52.7 while after the service (post-test) obtained an average score of peer conformity = 84.5. From the results of the study it can be concluded that there is an influence of the use of assertive training techniques to reduce peer conformity in class VII Medan Daughter Middle School Academic Year 2012/2013. This was tested using the t test obtained from calculations with the results of tcount = 2.22719> ttable = 2.13, so the hypothesis proposed was